Bridging the Gap: Methodological Insights From Cognitive Science for Enhanced Requirement Gathering (Journal of Science & Technology, 2020)
This review paper critically examines methodological insights derived from cognitive science to refine and optimize the process of requirement gathering in various domains. With a focus on the intersection between cognitive science principles and requirement engineering, this paper aims to unravel strategies that enhance accuracy, comprehension, and communication throughout the requirement gathering phase. By synthesizing findings from diverse studies, this review contributes to a deeper understanding of how cognitive science methodologies can be strategically applied to improve the efficacy of requirement gathering processes. he successful bridging of the gap between learning spaces could further benefit from including more online social learning activities into the designed learning process and from involving teachers as cocreators of the learning process and resources.